2019
DOI: 10.1186/s13613-019-0562-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and impact of sepsis on long-term outcomes after subarachnoid hemorrhage: a prospective observational study

Abstract: Background Aneurysmal subarachnoid hemorrhage (SAH) is an acute cerebrovascular disease associated with high mortality and long-term functional impairment among survivors. Systemic inflammatory responses after acute injury and nosocomial infections are frequent complications, making the management of these patients challenging. Here, we hypothesized that sepsis might be associated with early and long-term mortality and functional outcomes. Our objective was to define the incidence of sepsis, diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 33 publications
5
28
0
Order By: Relevance
“…In the clinical setting, brain injury-associated infections are associated with poor outcomes. 1,2,5,15 For example, a high proportion of CSF neutrophils has been associated with the occurrence of vasospasm after SAH. 16,17 However, it remains controversial Blood inflammatory markers were measured on days 1 to 3, 4 to 5, and 6 to 7 after SAH onset in patients without ventilator-associated pneumonia (white boxes, n=10) and with ventilator-associated pneumonia (gray boxes, n=6).…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical setting, brain injury-associated infections are associated with poor outcomes. 1,2,5,15 For example, a high proportion of CSF neutrophils has been associated with the occurrence of vasospasm after SAH. 16,17 However, it remains controversial Blood inflammatory markers were measured on days 1 to 3, 4 to 5, and 6 to 7 after SAH onset in patients without ventilator-associated pneumonia (white boxes, n=10) and with ventilator-associated pneumonia (gray boxes, n=6).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of infectious patients will rapidly deteriorate and finally develop sepsis, due to systemic metabolic disorders and stress caused by excessive release of inflammatory factors and immunosuppression after ICH (Berger et al, 2014;Cheng et al, 2018). Clinically, sepsis complicated by the ICH is common but tricky in the neurosurgical intensive care unit and kills as many as a half (Goncalves et al, 2019). Our retrospective cohort study has shown that approximately 28% of patients with ICH would accompany sepsis, and sepsis is the leading cause of poor outcomes.…”
Section: Introductionmentioning
confidence: 93%
“…Sepsis-1 presence of ≥2 SIRS criteria within an infection period 1 [15] sepsis according to Sepsis-1 + norepinephrine ≥ 0.1 µg/kg/min Sepsis-3_orig acute change in SOFA_orig ≥ 2 within an infection period 1 [8] sepsis according to Sepsis-3_orig + norepinephrine ≥ 0. 1) within an infection period 1 sepsis according to alternative sepsis criteria + dysfunction of cardiovascular system according to criteria (Table 1) + lactate > 2 mmol/L Systemic Inflammatory Response Syndrome (SIRS), Sequential Organ Failure Assessment (SOFA); 1 To ensure comparability for evaluation of sepsis criteria, a time frame of 4 days around infection onset was implemented (including 2 days before the onset of infection, the day of infection onset itself, and 1 day after) as validated for robustness by Verboom et al [30]). Sepsis was considered present if the respective criteria were fulfilled within this 4-day window around infection onset.…”
Section: Sepsis Criteria Septic Shock Criteriamentioning
confidence: 99%
“…More than 30% of patients with a spontaneous subarachnoid hemorrhage (SAH) develop infections during their hospitalization [1][2][3], and sepsis was identified as an independent risk factor for the impaired functional outcome [1,[4][5][6]. Nevertheless, data on infectious complications and sepsis in patients with an SAH remain scarce, resulting in the need for further investigations [1,7].…”
Section: Introductionmentioning
confidence: 99%